Red Blood Cell Distribution Width: A Prognostic Marker in Patients With Type B Aortic Dissection Undergoing Endovascular Aortic Repair - Jiang, Cheng; Liu, Anbang; Huang, Lei; Liu, Quanjun; Liu, Yuan; Geng, Qingshan (Frontiers in Cardiovascular Medicine, 2022)
Background Red blood cell distribution width (RDW) is associated with cardiovascular mortality. However, the relationship between preoperative RDW and outcomes after thoracic endovascular aortic repair (TEVAR) in type B aortic dissection (TBAD) remains to be determined. Methods We review the records of 678 patients with TBAD and treated with TEVAR in three centers. Patients were divided into two groups according to the admission RDW cut-off by receiver operating characteristic curve analysis [≤13.5% (n = 278) and >13.5% (n = 400)]. The association between RDW and long-term mortality was evaluated using Cox survival analysis. Additionally, we used general additive models (GAM) with restricted cubic splines (RCS) to explore non-linear relationships between RDW and outcomes. Results Subjects with a high RDW had significantly higher in-hospital mortality rates (1.4 vs. 4.3%, P = 0.038). A total of 70 subjects died after a median follow-up period of 3.3 years. Kaplan–Meier analysis showed that subjects with an RDW >13.5% had worse survival rates than those with lower RDW values (P < 0.001). Multivariate Cox proportional hazard modeling revealed that an RDW >13.5% was an independent predictor of long-term mortality (adjusted HR = 2.27, P = 0.006). Also, we found that there was a non-linear relationship between RDW and mortality from RCS, and RDW of 13.5% might be an inflection point to distinguish the long-term mortality risk of TBAD patients. Conclusion As an inexpensive and routinely measured parameter, RDW holds promise as a novel prognostic marker in patients with TBAD receiving TEVAR. We found that an RDW >13.5% on admission was independently associated with increased long-term mortality.